(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
Digital educational resources are modern technical tools, which are designed to improve and improve the quality of students’ knowledge. The inclusion of these resources in the educational process forms positive learning motivation of students, stimulates creative cognitive activity, the need for independent education.